English endearments in Elizabeth Gilbert’s Eat Pray Love: the factors and functions - Giyatmi, Giyatmi; Arumi, Sihindun (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2022)
ABSTRACT This study aims at explaining the factors influencing the use of endearment and their functions in the novel Eat Pray Love (EPL) by Elizabeth Gilbert. This study uses Wardhaugh's theory to describe the factors influencing the selection of endearment and Yang's theory to describe their function. This is descriptive research that deals with the use of endearments in the novel. The data of the research is endearments in EPL. The writers used documentation and content analysis in data collection. Data analysis techniques included data collection, reduction, display, and conclusion drawing. The researcher applied source and theoretical triangulation. The researchers found 18 endearments in EPL. The factors influencing the choice of endearment are the degree of intimacy (66,6%), family (16,6%), and particular occasion (16,6%). There are 4 functions of endearment namely; showing closeness (55,5%), showing identity (22,2%), getting attention (16,6%), and showing respect (5,5%). From the results of the study, it can be seen that the most dominant factor determining the use of endearment is the degree of intimacy as it is mostly used by people with a high degree of intimacy such as lovers, close friends, and family. Meanwhile, its most dominant function is to show closeness as a result of the high level of intimacy between the speaker and listener.